2020
DOI: 10.3389/fchem.2020.00829
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin as Tumor Suppressor in Cancers: Biotherapeutic Activity, Nanodelivery, and Mechanisms With Emphasis on Pancreatic Cancer

Abstract: Pancreatic cancer is the most lethal malignancy of the gastrointestinal tract. Due to its propensity for early local and distant spread, affected patients possess extremely poor prognosis. Currently applied treatments are not effective enough to eradicate all cancer cells, and minimize their migration. Besides, these treatments are associated with adverse effects on normal cells and organs. These therapies are not able to increase the overall survival rate of patients; hence, finding novel adjuvants or alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 246 publications
(224 reference statements)
0
56
0
Order By: Relevance
“…Apigenin is one of the most abundant flavonoids in plant kingdom and therefore has been the target of various investigations for its use as anticancer agent and for its role in cancer prevention [ 102 , 103 , 104 ]. In these studies, the compound showed anticancer potential via induction of apoptosis and cell cycle arrest as well as the downregulation of matrix metalloproteinases and interaction with miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Apigenin is one of the most abundant flavonoids in plant kingdom and therefore has been the target of various investigations for its use as anticancer agent and for its role in cancer prevention [ 102 , 103 , 104 ]. In these studies, the compound showed anticancer potential via induction of apoptosis and cell cycle arrest as well as the downregulation of matrix metalloproteinases and interaction with miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Increased glutamine metabolism also protects cells from elevated oxidative stress. Numerous reports have discussed the potential for metabolic stress leading to increased oxidative stress [147,[149][150][151][152][153]. Transcription factor EB (TFEB) has attracted a lot of interest recently for its ability to regulate PDAC growth.…”
Section: Involvement Of Metabolic Stress In Pdacmentioning
confidence: 99%
“…Similar to chrysin, apigenin is a potent anti-tumor agent against various cancers including breast cancer, lung cancer and gastric cancer [ 7 ]. Apigenin impairs progression of multiple myeloma cells in a dose-dependent manner.…”
Section: Dietary Agents and Cancer Stem Cellsmentioning
confidence: 99%
“…Regardless of cancer incidence rate and cell deaths, there have been efforts in developing novel therapeutics for tumor treatment [ 3 , 4 , 5 , 6 ]. Surgery or tumor resection is beneficial in early stages of cancer and when tumor cells diffuse into various tissues in body, it is impossible to eliminate cancer by using surgery [ 7 , 8 ]. Radiotherapy is less invasive compared to surgery, but it has its own problems including side effects and risk of resistance [ 9 ].…”
Section: Introductionmentioning
confidence: 99%